A study on an implementation of ergonomics working environment at Majlis Perbandaran Muar - Norisam, Nurul Atikah (2010)
This study is focus on an implementation of ergonomics working environment. The first objective of this research is to study about the implementation of ergonomics working environment at Majlis Perbandaran Muar. Secondly the objective is to determine the most dominant factors that contribute to the implementation of ergonomics working environment. Lastly the objective of this research is to propose soma recommendation in order to help the management to overcome the problem faced. All the objectives were using different method in analyze the result. For the first objective, the researcher used descriptive analysis in order to get the result. So, it shows that the Majlis Perbandaran Muar was implementing the ergonomics working environment. Then, the researcher used stepwise regression in order to know the most dominant factor that contributes to the implementation. It shows that the physical environment is the variable that most contribute to the implementation of ergonomics working environment at Majlis Perbandaran Muar.The researcher also provides some suggestion to solve some problem arise. The researcher would suggest that the organization should provide awareness programme to educate the staffs. In addition, the researcher also recommend that workers need to participate in all programme provide by the organization. The organization should provide ergonomics training to the workers in order to avoid them from suffering any injuries. Finally, the researcher also suggests that the communication also important as a medium in implementing ergonomics working environment.